2011
DOI: 10.1111/j.1349-7006.2011.02134.x
|View full text |Cite
|
Sign up to set email alerts
|

IDH mutations predict longer survival and response to temozolomide in secondary glioblastoma

Abstract: Recent studies have shown that isocitrate dehydrogenase1 ⁄ 2 (IDH1 ⁄ 2) mutations occur frequently in secondary glioblastoma. This study aimed to investigate their impact on temozolomide chemosensitivity and relationship with O(6)-methylguanine DNA methyltransferase (MGMT) promoter methylation in secondary glioblastoma. Searches for IDH1 and IDH2 mutations, 1p19q codeletion, MGMT promoter methylation, and p53 expression were carried out in a series of 86 secondary glioblastomas and correlated with progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
205
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(225 citation statements)
references
References 34 publications
(53 reference statements)
10
205
0
2
Order By: Relevance
“…3). IDH1/2 mutations have been associated with overall better prognosis across all diffusely infiltrating malignant astrocytic entities (9,10,12,15,16) and their absence in elderly glioblastoma patients may explain in part why age is a negative prognostic factor in this disease (17). However, it has never been explored whether tumors with IDH1/2 mutations are enriched in long-term survivors of glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…3). IDH1/2 mutations have been associated with overall better prognosis across all diffusely infiltrating malignant astrocytic entities (9,10,12,15,16) and their absence in elderly glioblastoma patients may explain in part why age is a negative prognostic factor in this disease (17). However, it has never been explored whether tumors with IDH1/2 mutations are enriched in long-term survivors of glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…The robustness of IDH1 mutation and MGMT methylation may drive other genetic changes in tumor cells, tumors accompanied by IDH1 mutation and methylated MGMT may consequently have different genetic characteristics compared to tumors unaccompanied by the alternations, which may lead to their varied biological features and patients' survival. As previous reported that the survival time of glioblastoma patients with only IDH1 mutation is shorter than that for patients with both IDH1 mutation and MGMT methylation (Hartmann et al, 2010;Juratli et al, 2012;SongTao et al, 2012). It is suggested that the IDH1-mutated patients is not homogeneous and that the prognosis is not only depend on IDH1 mutation but also on MGMT methylation, so there may be a underlying mechanistic link between IDH1 mutations and MGMT methylation and needs to be further explored (Wick et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, the presence of an IDH mutation predicts response to temozolomide in low-grade gliomas and secondary glioblastomas. 11,26 In contrast, little reliable information is available to demonstrate any difference in the impact of the extent of resection in glioma with a mutated and wild-type IDH1/IDH2 gene. If any difference between glioma with mutated or wild-type IDH genes can be demonstrated in the future, an intraoperative molecular diagnosis will provide useful information for designing the surgical strategy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, the mutations have been shown to be prognostic 1,20,25 in high-grade gliomas and we can expect them to be present after radiation therapy and chemotherapy. 11,26,29 Based on these findings, we considered that the intraoperative detection of these mutations has potential for clinical application.…”
Section: Abstract • Glioma • Intraoperative Molecular Diagnosis • Idmentioning
confidence: 99%